Pengelompokkan Wilayah Berdasarkan Variabel-Variabel Kemiskinan di Provinsi Aceh dengan Metode Average Linkage Hierarchical Clustering - Wahyudi, Muhammad Rafidzaky; Siagian, Tiodora Hadumaon (Politeknik Statistika STIS, 2024)
The big problem facing the Indonesian government is poverty. Aceh Province is one of the poorest provinces in Indonesia. It ranked 6th and even became the poorest province in the Western region of Indonesia. This condition is quite pathetic considering that Aceh is a province that has special autonomy and quite a large regional income, making it one of the richer provinces. Therefore, this study aims to cluster regions in Aceh Province based on poverty variables using the average linkage hierarchical clustering method and compare the results in 2017 and 2022. The results of the study show that the clustering results in 2017 are no different from 2022. Two clusters were formed, Cluster 1 consists of 3 districts with low poverty levels, and Cluster 2 consists of 20 districts with high poverty levels. This explains that in the 2017–2022 Aceh government period, areas with high poverty levels remain in the high poverty category, and vice versa. It means that the poverty alleviation efforts carried out by the Aceh government during that period have not been able to optimally improve the welfare of the Acehnese population.